2012
DOI: 10.1111/pace.12048
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Cardiac Resynchronization Therapy in the Elderly

Abstract: Octogenarian patients who received CRT with or without a defibrillator for advanced heart failure had similar clinical benefits as younger patients. CRT should not be withheld from octogenarians meeting current selection guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 29 publications
4
26
0
Order By: Relevance
“…Hospital and Provider Characteristics for Different Age Groups for Those Undergoing ICD Implantation (With or Without CRT)Although our study did not examine complication rates, other investigations have found complication rates for older patients are comparable to those for younger patients(10,17,18). Although in-hospital death is higher with older age, device-related complications requiring surgical intervention were <3% at 1 year regardless of age(14).Other registries have noted less use of CRT in the elderly(19,20).…”
mentioning
confidence: 56%
“…Hospital and Provider Characteristics for Different Age Groups for Those Undergoing ICD Implantation (With or Without CRT)Although our study did not examine complication rates, other investigations have found complication rates for older patients are comparable to those for younger patients(10,17,18). Although in-hospital death is higher with older age, device-related complications requiring surgical intervention were <3% at 1 year regardless of age(14).Other registries have noted less use of CRT in the elderly(19,20).…”
mentioning
confidence: 56%
“…Our rate of implant-related complications is similar to the one reported by the COMPANION investigators [2], who found these adverse effects in 8 % of their population of younger individuals than ours. Furthermore, recent studies show a similar rate of complications in young and elderly patients [24,27], with a very low rate of significant complications (associated with surgical reinterventions at 1 year <3 % regardless of age [27]). Thus, elderly patients have a low rate of procedure-related complications and this rate is similar to that of young patients.…”
Section: Discussionmentioning
confidence: 85%
“…However, no randomized controlled trials have addressed the value of CRT in elderly HF patients [22][23][24][25][26]. Elderly HF patients (≥75 years) have been underrepresented or excluded in the aforementioned CRT trials despite the fact that HF is more prevalent in the very elderly as compared with younger patients [1].…”
Section: Discussionmentioning
confidence: 97%
“…(47) Comparable findings were also reported in subgroup analyses involving patients from COMPANION, (32) CARE-HF (33) and several cohort studies. (48)(49)(50) Device-related complication rates did not differ across age groups. In a COMPANION subgroup analysis, there was no significant difference in survival rates between elderly and non-elderly patients.…”
Section: Cardiac Resynchronisation Therapymentioning
confidence: 85%